Empirical prediction of thermal properties, microhardness and sound velocity of cubic zinc-blende AlN - Daoud, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2019)
Based on some empirical formulas and some data reported in the literature, this contribution aims to study the correlation between several physical properties of cubic zincblende aluminium nitride (c-AlN) semiconducting material. So, we report an empirical prediction at room temperature of the Debye temperature, Debye frequency, melting temperature, thermal conductivity, Vickers hardness, and sound velocity of c-AlN. Our calculated results are compared with other data from the literature; they are in very good agreement with other data previously published. At room temperature, the Debye temperature was found at around 978.84 K, the thermal conductivity is 3.82 W⋅cm⁻¹⋅K⁻¹, while the melting temperature is around 2967.4 K, respectively. The deviations of the Debye temperature and melting temperature between our obtained values and the theoretical ones in the literature are less than 0.92% and 1.1%, respectively. Our findings on the different quantities of the zinc-blende phase have been compared to those of the hexagonal wurtzite phase. In general, no significant differences in the different quantity values between zinc-blende and wurtzite phases of the AlN compound have been observed.